2022
DOI: 10.1002/adfm.202205106
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Plasma‐Assisted Growth of Large‐Area MoS2 for Transparent Phototransistors

Abstract: MoS2‐based transparent electronics can revolutionize the state‐of‐the‐art display technology. The low‐temperature synthesis of MoS2 below the softening temperature of inexpensive glasses is an essential requirement, although it has remained a long persisting challenge. In this study, plasma‐enhanced chemical vapor deposition is utilized to grow large‐area MoS2 on a regular microscopic glass (area ≈27 cm2). To benefit from uniform MoS2, 7 × 7 arrays of top‐gated transparent (≈93% transparent at 550 nm) thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…To meet the increasing demand for large data processing and storage, developing alternate computing hardware for beyond-complementary-metal-oxide-semiconductor electronics is essential . The next-generation storage devices are crossbar arrays of memory cells known for their high density, rapid operation, and multilevel conductance during low-power operation. The performance of memristors utilizing transition-metal oxides and organic molecules has advanced tremendously; however, they fail to meet energy efficiency requirements, easy fabrication, and computational tasks. In contrast, memristors based on two-dimensional (2D) materials exhibit excellent performance owing to their controllable van der Waals gaps, defect-free surfaces, exceptional thermal and mechanical stability, and promising resistive switching (RS) behavior with a high RS ratio and low switching voltage. Several studies have been conducted employing 2D layered materials such as MoS 2 , HfSe 2 , etc. to fabricate crossbar memristors via mechanical exfoliation, which limits the thickness uniformity over a large area, resulting in locally limited performance or variable performance characteristics. , Therefore, considerable efforts have been made to fabricate large-area crossbar memristor arrays by liquid-phase exfoliation and spin coating; however, limitations in area scaling and uncontrollable morphology lead to poor endurance and device density. , …”
Section: Introductionmentioning
confidence: 99%
“…To meet the increasing demand for large data processing and storage, developing alternate computing hardware for beyond-complementary-metal-oxide-semiconductor electronics is essential . The next-generation storage devices are crossbar arrays of memory cells known for their high density, rapid operation, and multilevel conductance during low-power operation. The performance of memristors utilizing transition-metal oxides and organic molecules has advanced tremendously; however, they fail to meet energy efficiency requirements, easy fabrication, and computational tasks. In contrast, memristors based on two-dimensional (2D) materials exhibit excellent performance owing to their controllable van der Waals gaps, defect-free surfaces, exceptional thermal and mechanical stability, and promising resistive switching (RS) behavior with a high RS ratio and low switching voltage. Several studies have been conducted employing 2D layered materials such as MoS 2 , HfSe 2 , etc. to fabricate crossbar memristors via mechanical exfoliation, which limits the thickness uniformity over a large area, resulting in locally limited performance or variable performance characteristics. , Therefore, considerable efforts have been made to fabricate large-area crossbar memristor arrays by liquid-phase exfoliation and spin coating; however, limitations in area scaling and uncontrollable morphology lead to poor endurance and device density. , …”
Section: Introductionmentioning
confidence: 99%
“…The broadened line width of Raman spectra and extended tail region of the E 1 2g peak at lower frequency reflect the smaller grain size of the synthesized MoS 2 film. 22 In addition, Raman intensity mapping of E 1 2g and A 1g is performed by scanning over a 20 × 20 μm 2 area (Figure 2c,d); less variation in intensity distribution in Raman mapping micrographs reveals the uniformity in terms of thickness and crystallinity of the low-temperature-grown MoS 2 film. Furthermore, the uniformity of the MoS 2 film over a large area was verified by obtaining Raman spectra at 64 different points across a 4 × 4 cm 2 area, as shown in Figure S1a−c (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In view of this, this study focused on the back-end-of-line (BEOL) compatible direct growth of a uniform large-area thin MoS 2 film on a prepatterned BE deposited on a flexible (polyimide (PI)) substrate at low temperature (250 °C) utilizing a radio frequency (RF) magnetron sputtering and plasma-enhanced chemical vapor deposition (PECVD) technique . The transition ( T g ) temperature of PI is ∼360 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect to point out is that the fabricated photodetector should show negligible hysteresis and minimum electrical gate stress effect, which may enable the more enhanced photodetector metrics in the devices comprising the complex fabrication processes. Although the annealing treatments, encapsulation, and different integration approaches fulfill the rising demand for highly sensitive photodetectors, this requires a complex and sophisticated fabrication process. We aim to investigate the alternative tactics to reduce the majority charge carrier trapping accompanying the enhanced photoresponsivity in the intrinsic MoS 2 under low-power illumination. Also, several reports have demonstrated that implementing gate bias pulses with an appropriate pulse width (PW) could successfully develop a trapping-free field-effect transistor. , To the best of our knowledge, the impact of pulsed gate bias on the photodetector metrics of the 2D materials has not been realized yet and needs to be explored.…”
Section: Introductionmentioning
confidence: 99%